Mechanochemical synthesis of CNT/ZnO hybrid materials - Siti Sumaiyah, S.A.A.; Nurhana Ilmira, H.; Nunshaimah, S.; Syamsyir Akmal, S.; Azhan, H.; Siti Nor Hafiza, M.Y.; Yusoff, M.A.; Roslan, M.N. (2014)
A study on the synthesis of multiwalled carbon nanotubes (MWCNT) and zinc oxide (~no) hybrid materials using the mecahnochemical technique has been conducted. MWCNT was dispersed in sodium dodecyl sulfate (SDS) solution. ZnO was formed at milling time of2, 5 and 10 hours. The XRD results showed only small peaks of ZnO. This suggests that at longer milling time, the ZnO crystals were either become amorphous or have reduced in sized so as not to be detected Using XRD. ZnO has also been doped with Manganese (Mn) which have affected the crystal structure and surface morphology of the sample. In summary, we have demonstrated a simple and efficient technique for producing CNT/ZnO hybrid materials that may have enhanced applications as chemical sensors, fuel cell electrodes and piezoelectric generators.